Exploring SARS-CoV-2 and Plasmodium falciparum coinfection in human erythrocytes - López-Farfán, Diana; Irigoyen, Nerea; Gómez-Díaz, Elena (Frontiers in Immunology, 2023)
The co-occurrence and the similarities between malaria and COVID-19 diseases raise the question of whether SARS-CoV-2 is capable of infecting red blood cells and, if so, whether these cells represent a competent niche for the virus. In this study, we first tested whether CD147 functions as an alternative receptor of SARS-CoV-2 to infect host cells. Our results show that transient expression of ACE2 but not CD147 in HEK293T allows SARS-CoV-2 pseudoviruses entry and infection. Secondly, using a SARS-CoV-2 wild type virus isolate we tested whether the new coronavirus could bind and enter erythrocytes. Here, we report that 10,94% of red blood cells had SARS-CoV-2 bound to the membrane or inside the cell. Finally, we hypothesized that the presence of the malaria parasite, Plasmodium falciparum, could make erythrocytes more vulnerable to SARS-CoV-2 infection due to red blood cell membrane remodelling. However, we found a low coinfection rate (9,13%), suggesting that P. falciparum would not facilitate the entry of SARS-CoV-2 virus into malaria-infected erythrocytes. Besides, the presence of SARS-CoV-2 in a P. falciparum blood culture did not affect the survival or growth rate of the malaria parasite. Our results are significant because they do not support the role of CD147 in SARS-CoV-2 infection, and indicate, that mature erythrocytes would not be an important reservoir for the virus in our body, although they can be transiently infected.